Evaluation of the impact of diabetes education via social media on glycemic control of patients with type 1 Diabetes mellitus during the COVID-19 pandemic (Research, Society and Development, 2022)
Introduction: Diabetes mellitus (DM) is an important public health problem worldwide. Diabetes structured education must be part of treatment. Objective: Evaluate the use of a social media-based diabetes education and its impact on glucose control. Methods: Randomized clinical trial of type 1 DM outpatients followed at a public health reference clínic of Federal District, Brazil. Participants were randomized to receive diabetes education vídeo via social media (WhatsApp®) or educational information during outpatient consultations, for a period of 12 weeks. The Diabetes Knowledge Scale Questionnaire was applied and results of glycated hemoglobin (HbA1c) and data from glucose managemenst softwares were collected before and after the intervention. Results: 193 participants completed the study, 95 from the intervention group and 98 from the control group. There was an improvement in the questionnaire score in both groups: intervention (p < 0.001) and control (p = 0.021). Regarding glucose control, there was no statistically significant difference when comparing HbA1c and electronic glucose management data between the two groups. Conclusion: It was not possible to establish a relationship of superiority of the strategy used, compared to educational information during outpatient consultations, in improving knowledge about DM. The collected data also suggest that the availability of educational material via WhatsApp® alone does not promote improvement in glucose control.